Inclusive LGBTQIA+ healthcare: An interprofessional case-based experience for cultural competency awareness - Prasad, Samiksha; O'Malley, Chasity B.; DeLeon, Rolando; Levy, Arkene S.; Griffin, Daniel P. (Frontiers in Public Health, 2023)
Introduction Lesbian, Gay, Bi-sexual, Transgender, Questioning, Intersex, and Asexual (LGBTQIA+) patients report experiences of discrimination within healthcare settings due to a lack of provider knowledge and biases of healthcare workers. There is an identified need among all health professions to provide more culturally competent healthcare for this community. Early interventions during healthcare profession training programs may be effective to address this need. The overall goal of this study was to assess the educational impact of an active learning session that was specifically designed to enhance LGBTQIA+ cultural competency awareness using an interprofessional setting. Methods This 2-year study involved students from 16 healthcare professional programs joining virtually to form interprofessional teams. A small group case-based learning approach was used and included pre/post-activity surveys to measure the change in student attitude and confidence, as well as the change in perception of the importance of the activity. Results Results indicate an increase in perception of importance (p < 0.005) and in overall level of confidence (p < 0.001) with respect to LGBTQIA+ issues post-session. Key themes established through the session represent an overall recognition of the importance of interprofessional education and awareness of LGBTQIA+ healthcare needs. Discussion The results demonstrate the effectiveness of a case-based approach for enhancing cultural competency awareness across different healthcare professions programs. This session also provided an interprofessional learning environment to allow multiple healthcare professions program students to interact and share perspectives. The positive impact of this intervention in a highly collaborative virtual learning environment also highlights that this immersive active learning approach that can be adopted across different programs and institutions.